STUDI KOMPARASI KECERDASAN EMOSIONAL BERDASARKAN TINGKAT PRESTASI AKADEMIK MAHASISWA PROGRAM STUDI S1 FARMASI UNIVERSITAS SARI MUTIARA INDONESIA - Meliala, Sinarsi; Tobing, Laksana; Ningsih, Siska Dwi; Timoty, Ivan (JURNAL PSYCHOMUTIARA, 2022)
Students’ issues in maintaining motivation, dividing study and play time, having no goals, being unable to cope with lecturer pressure, laziness, and other factors such as family environment can be an obstacle in achieving a GPA. GPA, on the other hand, is significant because it can serve as a first impression and a key role in securing employment. As a result, in addition to having great academic intelligence, students must also be able to overcome challenges, understand emotions, and regulate their emotions in order to fully utilize their learning talents. This research is entitled "Comparative Study of Emotional Intelligence Based on Academic Achievement Level of Students of the Bachelor of Pharmacy Study Program, Sari Mutiara University of Indonesia" with the aim of determining the differences or comparisons between students' emotional intelligence and their academic accomplishment levels. The researcher's measuring tool is based on Daniel Goleman's five characteristics of emotional intelligence: detecting one's own emotions, controlling emotions, motivating oneself, understanding other people's emotions, and developing relationships. The respondents in this study were 84 active students of Sari Mutiara University's Pharmacy Study Program in Indonesia. The research was descriptive in nature, with a comparative study design. The validity of the items was determined by the measuring device to be in the range from 0.218 to 0.480. The emotional intelligence measuring instrument employed in this study had a reliability of 0.886. According to the findings of a survey of 84 students, a high degree of student academic accomplishment is closely linked to their emotional intelligence. It is suggested that future researchers deal with a bigger number of samples while employing more diversified variables.